التصوف الإسلامي المعاصر برؤية الطريقة الكسنزانية: Contemporary Islamic Sufism from The Perspective of The Kasanzaniyyah Order - Abu Younis, Qais; Asha'ari, Muhamad Faisal; Abdul Ghani, Mohamad Zulkifli; Mohamad, Abu Dardaa (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
Sufism has become a focal point for researchers seeking its invaluable benefits, as it offers solutions to numerous societal problems. This study explores modern Sufism, particularly amidst the intellectual turmoil and conflicts prevalent in contemporary societies. Emphasizing modern Sufism’s ability to nurture hearts and cultivate good values and morals is crucial in such contexts. While many Sufi groups worldwide focus inwardly on the soul and heart, al-Tariqah al-Kasanzaniyyah offers a modern Sufism perspective and method capable of addressing contemporary challenges. This study aims to present the concepts adopted by al-Tariqah al-Kasanzaniyyah in treating hearts and reforming societies through its integrated Sufism approach, serving as a model for other Sufi tariqats. The researcher employed an interview as a research method to collect authentic information, including personal interviews with the Shaykh of the tariqah and its students. In addition, the descriptive-analysis method is used to analyze the writings about Tariqah al-Kasanzaniyyah and the teachings of the shaykh. The study concludes that Sufism, according to Shaykh Muhammad al-Muhammad al-Kasanzan, aims to fulfill the objectives of the Muhammadiyah message at all life levels, from individuals to society, thereby achieving the essence of the Islamic message and spreading goodness, mercy, and love for all humanity.